Insight Into Whole Genome of Aeromonas veronii Isolated From Freshwater Fish by Resistome Analysis Reveal Extensively Antibiotic Resistant Traits - Sakulworakan, Rungnapa; Chokmangmeepisarn, Putita; Dinh-Hung, Nguyen; Sivaramasamy, Elayaraja; Hirono, Ikuo; Chuanchuen, Rungthip; Kayansamruaj, Pattanapon; Rodkhum, Channarong (Frontiers in Microbiology, 2021)
Aeromonas veronii outbreaks in tilapia farming caused relatively high mortalities, and the bacteria was resistant to many kinds of antimicrobials used in Thailand aquaculture. According to the CLSI standard, the determination of antimicrobials efficacy has been limited to phenotypic analyses, and a genomics study is required. This research aimed to analyze the resistome of A. veronii isolated from diseased tilapia in Chainat, Nong Khai, and Uttaradit provinces in Thailand. A total of 12 isolates of A. veronii were identified based on the gyrB sequencing and then, the MIC values to eight antimicrobials (AMP, AML, GEN, ENR, OXO, OTC, SXT, and FFC) were determined. According to the MIC patterns, whole genome sequencing (WGS) of five representatives and resistome analysis were performed, including 15 genomes of A. veronii isolated from freshwater fish available in the NCBI. All tilapia isolates were susceptible to FFC but resistant to AML and AMP while OTC resistance was the most dominant. In addition to the WGS analysis, 4.5 Mbp of A. veronii was characterized. A total of 20 ARGs were detected by resistome analysis and 16 genes were shared among the A. veronii population. In conclusion, A. veronii strains isolated from tilapia exhibited a resistance to several antimicrobials and multidrug resistance (MDR) which was related to the presence of multiple ARGs. Aeromonas veronii shared the ARGs in their population worldwide with a possibility of a plasmid-mediated acquisition due to the presence of resistance islands.